PRAGMATIC STUDY IN THE FUNCTION OF DEIXIS IN KENNY ROGERS' SONG LYRICS - agustina maria rima widjajanti; Widiarsih Mahanani (LINGUAMEDIA Journal, 2022)
This paper aims to present the types of deixis and finding the effect deixis on the meaning of the song lyrics. The writer takes the data from five song lyrics of the Love of God album by Kenny Rogers. The type of research is descriptive qualitative method. In clarifying the type of deixis, the writer uses pragmatics analysis especially deixis theory. In finding out the effect deixis on meaning the writer applies deixis theory by Levinson. Then, the technique analyzing data, firstly in the analysis the data by representing the lyrics of the songs and all types of deixis. Secondly, analyzing the whole data based on the theory of deixis to get the answer of research question. Finally, the writer concludes the whole data analyzed by interpreting the result. The research finding of the study shows that there are five types of deixis, they are person, time, place, social and discourse deixis. The dominant deixis occurs in four songs lyrics are the first person and social deixis. In one song lyric, the first person and place deixis become dominant ones. The first person deixis is used to explain the speaker’ experience, the social deixis is taken to know the relation inside the song and the place deixis is applied to make the interpretation about place. The effect deixis on meaning as a whole in five song lyrics is that the hearers know the intention of the song lyrics. In four songs, these lyrics tell the speaker’ journey of faith to be close to God and in one song, the lyric tells the speaker’ experience in finding the right place on the religious community. It is reflected in the structure of language themselves, is through the phenomenon of deixis.